Chemically enhanced primary treatment of textile effluent using alum sludge and chitosan. Issue 16 (2nd April 2016) - Asif, Muhammad Bilal; Majeed, Nadeem; Iftekhar, Sidra; Habib, Rasikh; Fida, Sadia; Tabraiz, Shamas
Abstract: This study was conducted with the objective to develop a treatment system that can effectively reduce the elevated level of pollutants in textile effluent at primary stage of conventional wastewater treatment plant. Alum sludge, chitosan, and combination of alum sludge and chitosan coagulants were used as the replacement of conventional coagulants such as alum, etc. The performance of chemically enhanced primary treatment (CEPT) options was evaluated by measuring the supernatant residual total suspended solids (TSS), color, and chemical oxygen demand (COD) concentrations at various coagulants doses. In all CEPT options, TSS and color removal exceeded 95 and 85%, respectively. Use of alum sludge at the optimum dose of 400–500 ppm was not economical, due to high sludge production and higher cost associated with sludge disposal. Chitosan alone at optimum dose of 18 ppm resulted in enhanced COD removal as compared with other CEPT options. The use of chitosan in combination with alum sludge reduced the optimum dose of alum sludge and sludge production by 37.5 and 45.5%, respectively. Results also confirmed that CEPT options can also be used for decolorization of textile effluent.